Effective Factors for Promoting Student Engagement in Educational Activities - Darmal, Hassan Khan; Weyar, Sayed Shah Gul (Integrated Journal for Research in Arts and Humanities, 2024)
This study investigates the Effective Factors for Promoting Student Engagement in Educational Activities at the Faculty of Education, Helmand University. The research employed a quantitative approach and utilized a sample of (278) students from a total population of (995), selected using the Rao Soft Sample Size Calculator. The study had a (95%) confidence interval and a (5%) error level. The primary objective of this research was to explore the effective factors for promoting students engagement in educational activities. Two questionnaires were used, one focusing on students' educational activities and the other on teachers' emotional behavior. Simple linear regression was applied to analyze the effects of the independent variable (teachers' emotional behavior) on the dependent variable (students' educational activities), with data analyzed using SPSS and Excel. The findings indicate that teachers' emotional behavior significantly influences students' educational performance and activities. Specifically, the study found that teachers' strict and serious behavior (83%), establishing communication with students' parents (80%), and friendly and sincere relationships between students and teachers (76%) have notable effects on students' educational activities. This suggests that when teachers exhibit a gentle, sincere, friendly, and supportive attitude towards students during the teaching process, students are more likely to attend classes enthusiastically and actively participate in their lessons.